The impact of 21-hydroxylase deficiency on cardiac repolarization changes in children with 21-hydroxylasedeficient congenital adrenal hyperplasia - Korkmaz, Hüseyin Anıl; Özdemir, Rahmi; Küçük, Mehmet; Karadeniz, Cem; Meşe, Timur; Özkan, Behzat (The Turkish Journal of Pediatrics, 2019)
21-hydroxylase-deficient congenital adrenal hyperplasia (CAH) is associated with cardiovascular risk factors such as, hypertension, obesity, dyslipidemia, and insulin resistance. It is not known whether 21-hydroxylase-deficient CAH is risk factor for atrial and ventricular arrhythmias. The purpose of this study was to compare the 12-lead electrocardiographic measures in patients of 21-hydroxylase-deficient congenital adrenal hyperplasia with those in healthy control subjects matched for age, sex, height, weight and body mass index (BMI). Twenty-five patients with 21-hydroxylase-deficient CAH and twenty-five heathy control subjects were enrolled into this observational, cross-sectional, controlled study. The evaluation consisted of anthropometric measurements, biochemical parameters, and electrocardiographic (ECG) measures. The standard 12-lead electrocardiography was performed in all patients and P-wave dispersion (PWd), QT interval, QTd, QTcd, Tp-e dispersion, Tp-e/QT and Tp-e/QTc ratios were calculated. There were no significant differences in the groups for age, sex, height, weight and BMI (median age 9.4 (1.5-16.75) years, mean weight 37.6±21.5 vs. 27.9±18.3 kg, mean height 125.4±28.9 vs. 114.7±31 cm, mean BMI 21.4±5.7 vs. 18.9±3.4 kg/m2, respectively). P dispersion and Tp-e dispersion were significantly higher in patients of 21-hydroxylase-deficient CAH compared to the healthy subjects (median P dispersion 50 (25) vs. 40 (40) ms, mean Tp-e dispersion 48±15.5 vs. 35.2±17.5 ms). Our study revealed that 21-hydroxylase deficient CAH is associated with high risk of atrial and ventricular arrhythmias in children.